A Portray the Use of Speech Transitions in Semanticss and Pragmatics Class Presentation - Epi Wadison (Teaching English and Language Learning English Journal, 2024)
In presentation, speech transitions are words and phrases that allow someone to smoothly move from one point to another so that a presentation is unified and it is easier for the audience to understand an argument without confusing to how one point relates to another. The goal of this study is to investigate 21 English students using observation sheet when the students delivering presentation at Semantics and Pragmatics class. Data is described qualitatively to know the speech transitions used by students in one semester in academic year 20232 Key Words: Speech Transition, Semantics and Pragmatics class.